Health Political Communication After the Issuance of Presidential Regulation No. 18 Year 2016: a Case Study in RSUD Kabupaten Karawang - Nursanti, Siti; Dida, Susanne; Hidayat, Mien; Afriandi, Irvan (International Journal of Engineering and Technology, 2018)
Amendment to Government Regulation number 18 of 2016 begins with the issuance of Law Number 23 Year 2014 on Regional Instrument Organization to replace Law no.  32 year 2014.  In this study, researchers used qualitative methods with  Case Study approach, the researchers considered this method is very appropriate that best describe the phenomenon in political communication research related to post-implementation of Government Regulation No.  18 of 2016.  Ability to provide rich portraits which is the main benefit of case studies.  The research reader should be made to feel as if you were there with you in your research, see what you see, summarize what you have concluded. This research was conducted in Public Hospital Karawang regency.  In this study researchers found that: 1. Hospital changed the status that was originally Regional Technical Institute into Limited Service Unit Region under the health service 2. The Director is a physician or dentist whose functional status is then given an additional duty to become the Director of the Hospital 3. The Health Office is a member of the hospital supervisory board as well as the operational operator of the hospital has resulted an overlapping coordination in organizational communication